👤
DrAgOsH277
a fost răspuns

Cat da?vreau să mă verific

Cat Davreau Să Mă Verific class=

Răspuns :

Alitta
=>  3(4x²-4xy+y²) - (x²+4xy+4y²) + (x²+2xy+y²) =

      = 12x²-12xy+3y²- x²- 4xy - 4y²+x²+2xy+y² =

      = 12x² - 18xy 

 
Raisza
[tex]3({4x}^{2} - 4xy + {y}^{2}) - {x}^{2} + 4xy + {4y}^{2} + ( {x}^{2} + 2xy + {y}^{2} )[/tex]
[tex]12 {x}^{2} - 12xy + 3 {y}^{2} - {x}^{2} - 4xy - 4 {y}^{2} - {x}^{2} + 2xy + {y}^{2} [/tex]
[tex]12 {x}^{2} - 18xy[/tex]
(Gliseaza ca sa vezi raspunsul intreg)

Succes! :)